A study of the ferrallitic weathering of an amphibole schist in Peninsular Malaysia - Zauyah, S.; Stoops, G. (Universiti Pertanian Malaysia, 1990)
Micromorphological and mineralogical changes resulting from the weathering of an amphibole schist in Peninsular Malaysia have been studied. Although the hard bedrock mass is not reached, many large corestones of unweathered rock material are exposed. Thin sections and SEM observations show that the actinolite weathers faster than epidote. Both undergo congruent dissolution and are replaced by new formed vermiform kaolinite and halloysite in the lower saprolite, but by kaolinite and gibbsite in the upper saprolite. This data is corroborated by XRD studies. Chemical analyses of the weathering rims, expressed according to the isovolumetric method, show that they are already in the first stage of ferrallitic weathering with the alkaline and alkaline earth elements lost, as is a large part of the silicon, though aluminium remains practically constant. Iron accumulates during the first stage of weathering. The weathering front is abrupt, and pedoplasmation follows geological structures, forming a clay-rich soil material.